When virtual reality supports patients’ emotional management in chemotherapy - Buche, Hélène; Michel, Aude; Blanc, Nathalie (Frontiers in Virtual Reality, 2023)
Objectives: Our study is a follow-up of a previous research study that was carried out in physiotherapy. The present study aims to evaluate the effectiveness of virtual reality (VR) as a tool to support emotional management during the acute phase of breast cancer treatment (chemotherapy session).Materials and methods: A quasi-experimental protocol was implemented in an oncology department with 120 patients randomly assigned to one of four conditions that were being compared. During the first ten minutes of a chemotherapy session, patients could either be exposed to a participatory immersion in a natural environment; or be placed in a contemplative immersion condition in the same environment; or listen to classical music; or receive no distraction. The involvement of the patients in the virtual environment and the relevance of the immersive modalities were measured through the evaluation of sense of presence. Particular interest was given to the evaluation of anxiety level and the emotional state of the patients.Results: VR during chemotherapy reduces anxiety and calms emotional tension. The multi-sensory nature of this emotional regulation support tool was more effective than music in inducing positive emotion, and this benefit was the most salient when immersion was offered in an interactive format.Conclusions: The relevance of providing support through VR in oncology is confirmed in this study. This tool can compensate for the fluctuating availability of caregivers by offering patients the possibility of shaping their own relaxing worlds and could help preserve the patient-caregiver relationship.